The dam replacing gene product enhances Neisseria gonorrhoeae FA1090 viability and biofilm formation - Kwiatek, Agnieszka; Bacal, Pawel; Wasiluk, Adrian; Trybunko, Anastasiya; Adamczyk-Poplawska, Monika (Frontiers in Microbiology, 2014)
Neisseriacae do not exhibit Dam methyltransferase activity and, instead of the dam gene, possess drg (dam replacing gene) inserted in the leuS/dam locus. The drg locus in Neisseria gonorrhoeae FA1090 has a lower GC-pairs content (40.5%) compared to the whole genome of N. gonorrhoeae FA1090 (52%). The gonococcal drg gene encodes a DNA endonuclease Drg, with GmeATC specificity. Disruption of drg or insertion of the dam gene in gonococcal genome changes the level of expression of genes as shown by transcriptome analysis. For the drg-deficient N. gonorrhoeae mutant, a total of 195 (8.94% of the total gene pool) genes exhibited an altered expression compared to the wt strain by at least 1.5 fold. In Dam-expressing N. gonorrhoeae mutant, the expression of 240 genes (11% of total genes) was deregulated. Most of these deregulated genes were involved in translation, DNA repair, membrane biogenesis and energy production as shown by cluster of orthologous group analysis. In vivo, the inactivation of drg gene causes the decrease of the number of live neisserial cells and long lag phase of growth. The insertion of dam gene instead of drg locus restores cell viability. We have also shown that presence of the drg gene product is important for N. gonorrhoeae FA1090 in adhesion, including human epithelial cells, and biofilm formation. Biofilm produced by drg-deficient strain is formed by more dispersed cells, compared to this one formed by parental strain as shown by scanning electron and confocal microscopy. Also adherence assays show a significantly smaller biomass of formed biofilm (OD570= 0.242 +/- 0.038) for drg-deficient strain, compared to wild type strain (OD570= 0.378 +/- 0.057). Dam-expressing gonococcal cells produce slightly weaker biofilm with embedded in extracellular matrix cells. This strain has also a 5 times reduced ability for adhesion to human epithelial cells. In this context, the presence of Drg is more advantageous for N. gonorrhoeae biology than Dam presence.